Comparative Analysis of Fragile Fives with Panel VAR Models - Demirel, Esin; Akgül, Ş. Işıl (International Journal of Contemporary Economics and Administrative Sciences, 2023)
This study aims to show the similarities and differences between the fragile five classifications, which include countries that are quite different from each other, and to show whether there is a need for a different classification of fragile five, econometrically. In this context, the data set consists of old fragile five and new fragile five classifications. Seven independent variables that are thought to affect the gross domestic product of the countries have been determined. The data are annual for the period 2001-2018. Panel data analysis and Panel vector autoregression are used as a methodology in this paper, respectively. As a result of the analysis, the effects of the independent variables used in the analysis on the dependent differ in the countries included in fragile fives. Also, a change in one of the countries included in fragile fives will affect other countries. Therefore, it concluded that the variables in the models of fragile fives generally have different coefficients from each other. Based on this, it is understood that the revision of old fragile five does not conform to new fragile five, econometrically. It can be suggested as a policy implication that a different classification of fragile five is necessary.